(untitled) (African Journal of Biomedical Research, 2020)
Poor childcare practices among nursing mothers have been implicated as one of the factors influencing high child morbidity and mortality in many developing countries including Nigeria. Many health promotion and education approaches have been used in previous studies to improve childcare practices but very few have considered the inherent potentials of using faith-based strategy as one of the acceptable means of health promotion in many developing countries. This descriptive cross-sectional study was aimed at investigating the involvement of Pastors’ wives as change agents in educating nursing mothers on childcare practices in Ibadan North Local Government Area. Multi-stage sampling technique was used to select pastors’ wives from all the registered churches in the Local Government Area. A pre-tested interviewer-administered questionnaire was used for data collection. Data were analysed using descriptive and inferential statistics. One hundred and twenty-eight (N=128) pastors’ wives with age of 46.1±9.3 years were interviewed. Overall, 9.4% had never taught or preached on childcare practices or other health-related matters to mothers/women in the church before. Analysis showed that 42.2%, 26.6% and 31.3% of Pastor’s wives had good, fair and poor level of basic communication techniques, respectively. Age and educational status of Pastors’ wives significantly affect the level of communication between Pastors’ wives and mothers in the church (p<0.05). Involvement of Pastors’ wives with the mothers on childcare practices was through counselling (90.6%), teaching (53.1%), preaching (29.7%) and phone calls (18.8%). Counselling was the most preferred method (68.0%) of communication. This study establishes the fact that Pastors’ wives and nursing mothers have been communicating health matters through counselling, which can be used as an opportunity for improving child care through faith-based setting.